Nanomaterials engineering for enhanced low energy nuclear reactions: a comprehensive review and future prospects - Bakranov, Nurlan; Kuli, Zhanserik; Nagel, David; Bakranova, Dina (Frontiers in Materials, 2024)
This scientific paper aims to provide a thorough examination of the current state of research on nanomaterials in the context of Low Energy Nuclear Reactions (LENR). The paper explores various nanomaterials, their synthesis methods, and their impact on facilitating and enhancing LENR processes. Special attention is given to the unique properties of nanomaterials that make them particularly suitable for LENR applications, such as increased surface area, quantization effects, and improved hydrogen absorption kinetics. The review also delves into experimental findings and theoretical models that shed light on the mechanisms through which nanomaterials induce and support LENR. The sustained interest in LENR arises from experiments consistently demonstrating the potential for significant energy gains, suggesting cost-effective energy production. Furthermore, these processes exhibit advantages such as negligible radiation during operation, minimal radioactive waste, and the absence of greenhouse gas emissions. While the path to commercialization is lengthy, strides are being made by various companies recognizing the challenge of consistently producing materials to reliably trigger LENR. Current research focuses on employing nanoparticles to reliably induce LENR, drawing inspiration from reports indicating the efficacy of loose nanoparticles in triggering these reactions. The hypothesis posits that nanoparticles affixed to surfaces enhance performance and ease of handling in research and commercial setups. The rationale for using nanoparticles lies in their ability to facilitate hydrogen penetration into solid materials, crucial for observing LENR phenomena. This capability is attributed to the substantial surface area of nanoparticles, allowing them to absorb more reactants like hydrogen. Recent studies delve into understanding the behavior of metallic nanoparticles concerning the energy spectrum of electrons and implanted ions as a function of particle size. Notably, as nanoparticles decrease in size, quantization effects emerge, potentially modifying the interaction of quasiparticles within nanoclusters. Specific examples, such as Pd-Rh alloys, demonstrate accelerated hydrogen uptake kinetics in nanoparticles compared to bulk materials, emphasizing the importance of nanoscale properties. This topic provides a broad scope for exploring the intersection of nanomaterials and LENR, allowing for an in-depth analysis of the current state of research and the potential for future advancements. By understanding and harnessing the unique properties of nanomaterials, significant progress can be made in the field of LENR, potentially leading to practical and sustainable energy solutions.